Kebijakan Merdeka Belajar Serta Implementasinya Dalam Pembelajaran PAI di Sekolah (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2023)
This study aims to reveal the form of the Freedom to Learn policy proclaimed by the Minister of Education and Culture and its implementation in learning Islamic religious education (PAI) in schools. The method used in this study is a qualitative method with a library research approach. The research was conducted by reviewing various literature, both in the form of books, notes, and reports on the results of previous studies. Data literature study was collected through a process of scrutiny, analysis, and presentation of results. The results of this study indicate that there are 4 main principles of the Freedom to Learn Policy which include: 1) National standardized school exams (USBN) are developed by each school. 2) The national exam (UN) changes to a minimum competency assessment and character survey. 3) The freedom of educators to design learning implementation plans (RPP). 4) Flexibility in new student admission regulations (PPSB). Meanwhile, the implementation of the Independent Learning Curriculum in PAI learning at school includes three stages; 1) Learning Planning for Islamic Religious Education in this case is the preparation and development of learning tools. 2) Islamic Religious Education learning is carried out using independent flow, which stands for Starting from self, Concept exploration, Collaborative space, Guided reflection, Contextual demonstration, Elaboration of understanding, Connection between material, and Real action 3) Evaluation of Islamic Religious Education Learning is to develop formative and summative assessment. Evaluation can be carried out in the learning process (formative) and at the end of learning (summative).